Does predicted age at peak height velocity explain physical performance in U13-15 basketball female players? - Karol Gryko; Jakub Grzegorz Adamczyk; Anna Kopiczko; Jorge Lorenzo Calvo; Alberto Lorenzo Calvo; Kazimierz Mikołajec (BMC, 2022)
Abstract Background The aims of the study were (1) to identify the physical fitness and basic anthropometric characteristics of Polish female basketball players aged 13-15 years, (2) to show the effect of maturity timing on the performance in motor tests and basic body composition parameters, (3) to identify the index that contributes most to the prediction of performance in the tests of speed, jumping ability, agility, and endurance. Methods The sample included 904 female Polish players (U13-15). In part 1, maturity timing category distribution were examined within across age-groups. Maturity timing was followed by grouping with respect to years before or after the observed peak high velocity (PHV): PHV0 (− 0.50 to 0.49), PHV1 (0.50 to 1.49), PHV2 (1.50 to 2.49) and PHV3 (2.50 to 3.49). In part 2, the relationship between the anthropometric variables, physical fitness performance was assessed based on maturity timing categories (ANCOVA analysis). In part 3, backward stepwise multiple regression analyse quantified the relationship between maturity timing (group of PHV) and physical performance. Results ANCOVA results (age, body height, and body mass as covariates) showed in the U13 female basketball players significantly higher sprinting (20 m), jumping ability and endurance tests results of the PHV1 group. Better results was observed in U14 female players in PHV1 compared to PHV2 and PHV3 in 20 m and jumping tests but opposite trend was observed for 5 m sprint and endurance test (distance covered and VO2max). U15 basketball players from the PHV3 group were characterized by better results of jumping abilities, endurance, 10 m and 20 m sprint and agility (total, S4) tests. Maturity timing (10 m), chronological age (5 m, 20 m, agility, SVJ, VJ, and VO2max tests), body height (10 m), body mass (10 m, 20 m, VJ, VO2max), and the interaction between body mass and height (SVJ) were significant (adjusted R 2  = 0.02-0.10; p < 0.001) predictors of motor skills. Conclusion Trainng content of female basketball players aged 13-15 years old should be adjusted to biological requirements especially in jumping, endurance and 20 m sprint test. The time from peak height velocity (PHV) was a significant predictor only in the 10 m sprint test.